Pentingnya Pemahaman dan Penerapan SAK EMKM pada UMKM Kripik Sanjai Asia - Wiwik Andriani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study aims to provide education related to the preparation of financial statements at Kripik Sanjai Asia based on Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) using Microsoft Excel. This study used a qualitative approach, data was collected through observation, interviews, and documentation studies. The results showed that Kripik Sanjai Asia was still recording and processing data manually. The entity only has a record of cash in and out manually. So it cannot be known quickly and precisely whether the entity has a profit or loss. In this study, the researcher suggested to Kripik Sanjai Asia to use Microsoft Excel to make it easier for entities to prepare financial statements.